The influence of asthma onset and severity on malocclusion prevalence in children and adolescents - Luiz Sekio Tanaka; Cássia Cilene Dezan; Karen Barros Parron Fernandes; Flaviana Bombarda de Andrade Ferreira; Luiz Reynaldo de Figueiredo Walter; Alcindo Cerci Neto; Silvia Fernandes Chadi (Dental Press Editora, 2012)
OBJECTIVE: The influence of asthma, its severity levels and onset time on malocclusion occurrence were investigated. METHODS: The sample was composed by 176 children/adolescents, of both genders, aged 3 to 15 years, that were divided in two groups. The asthma group (AG) enrolled 88 children/adolescents that were seen at the Breathe Londrina Program. The asthma-free group (AFG) enrolled 88 preschool and school children recruited in 2 public schools. Malocclusion diagnosis was made according to WHO criteria (OMS, 1999). RESULTS: A higher prevalence in malocclusions in asthmatic patients in mixed dentition was observed when compared to controls (p<0.05). On the other hand, these results were not observed for deciduous (p>0.05) and permanent dentition (p>0.05). A significant association was seen between asthma onset time and marked maxillary overjet (p<0.05), and open bite (p<0.05) in the mixed dentition, being both conditions more common among those that have presented the symptoms of asthma prior to 12 months of age. CONCLUSION: The results of this study indicate that the early manifestation of asthma at first year of life can cause dentofacial changes. Therefore, the prompt diagnostic of the illness, as well as the establishment of a proper therapy could improve the symptoms and chronic complications of asthma and also reduce its impact on craniofacial development.